2018
DOI: 10.1002/eat.22976
|View full text |Cite
|
Sign up to set email alerts
|

Experimental manipulation of visual attention affects body size adaptation but not body dissatisfaction

Abstract: Objective: Prolonged exposure to large/small bodies causes aftereffects in perceived body size.Outside the laboratory, individuals repeatedly exposed to small (large) bodies tend to over-(under-) estimate their size and exhibit increased (decreased) body dissatisfaction. Why, among individuals exposed to approximately equivalent distributions of body sizes, only some develop body size and shape misperception and/or body dissatisfaction is not yet fully understood.Method: We exposed 61 women to high and low adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 64 publications
1
31
0
Order By: Relevance
“…We found no differences in VAS-or questionnaire-rated satisfaction with body size. These results fit with those described in another recent study [35]. In questionnaire measures of self-esteem and positive affect we found some suggestion that participants felt more positive in general after training with underweight bodies.…”
Section: Discussionsupporting
confidence: 92%
“…We found no differences in VAS-or questionnaire-rated satisfaction with body size. These results fit with those described in another recent study [35]. In questionnaire measures of self-esteem and positive affect we found some suggestion that participants felt more positive in general after training with underweight bodies.…”
Section: Discussionsupporting
confidence: 92%
“…There is now evidence that the magnitude and direction of the body-size and -shape aftereffect can be manipulated experimentally by directing young male and female participants’ visual attention toward certain stimuli. Thus, instructing participants to look at either the large or thin versions of simultaneously presented body-adaptation stimuli resulted in different directions of adaptation such that participants who were instructed to attend to the thin bodies experienced an “embiggening” aftereffect, whereas participants instructed to attend to the large bodies experienced an aftereffect of perceived size reduction (Stephen et al, 2019). 6…”
Section: In the Eye Of The Beholder: Explaining Individual Differencementioning
confidence: 99%
“…Similar results have been reported for high‐level aspects of complex stimuli such as facial identity (Rhodes et al , ). More recently, attentional effects have been shown in two empirical demonstrations of body size and shape aftereffects (Stephen et al , ; Stephen, Sturman, Stevenson, Mond, & Brooks, ). Although the source of the own‐gender bias demonstrated in this study cannot be confirmed, it seems likely that this could be explained by enhanced attention to own‐gender stimuli, resulting in larger aftereffects for these conditions.…”
Section: Discussionmentioning
confidence: 99%